The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.ecoinf.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of coastal lagoons in Tunisia: Ecological assessment to underpin conservation

Abstract: Ghar El Melh is a shallow lagoon (average depth of 0.8 m) that has undergone a eutrophication process due to growing human pressures. To obtain a global frame of the ecosystem functioning, an optical and an ecological classification were used in parallel. Downwelling and upwelling spectral irradiances were measured in situ in 22 sampling stations across the water body; then Apparent Optical Properties (AOPs), namely reflectance R(λ) and vertical attenuation coefficient K d (λ) were calculated for each waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The marine coastal ecosystems were characterized by highlyproductivity and critical ecology and economical functions with seagrasses, mangroves and coral reefs (Feng et al 2009;Nourisson et al 2013). The seagrass meadows with succession of aquatic angiosperms plants stabilize sediments reduce the velocity of flow and provide essential habitats for many estuarine species.…”
Section: Introductionmentioning
confidence: 99%
“…The marine coastal ecosystems were characterized by highlyproductivity and critical ecology and economical functions with seagrasses, mangroves and coral reefs (Feng et al 2009;Nourisson et al 2013). The seagrass meadows with succession of aquatic angiosperms plants stabilize sediments reduce the velocity of flow and provide essential habitats for many estuarine species.…”
Section: Introductionmentioning
confidence: 99%
“…As with K d , a marked variability of values and shapes was observed (Figure 4a), but some common features were identified. The values of R(10) in the green band [R(555)] were relatively high (1-19%, average 8.7%), indicating a conspicuous irradiance backscattering (see discussion in Nourisson et al 2013). The blue/green reflectance ratio [R(443) / R(555)] was always smaller than 1 (Nourisson et al 2013; Table 1), i.e.…”
Section: Optical Propertiesmentioning
confidence: 95%
“…The results from laboratory analyses (detailed in Nourisson et al 2013) showed that CDOM concentrations were relatively high (a CDOM (440) mean = 0.389 m −1 ; min. = 0.171, max.…”
Section: Las Concentrations and Patternsmentioning
confidence: 99%
See 2 more Smart Citations